1985
DOI: 10.1038/bjc.1985.256
|View full text |Cite
|
Sign up to set email alerts
|

Duration of ENNG administration and its effect on histological differentiation of experimental gastric cancer

Abstract: Summary An experimental trial in the induction of canine gastric cancers was conducted to study the relationship between the histological differentiation of adenocarcinoma and the duration of administration of the carcinogen, N-ethyl-N'-nitro-N-nitrosoguanidine (ENNG). Twenty-three adult Beagle dogs were divided into three groups according to the duration of administration. Over 3 months administration, the total dose of ENNG per animal was 5.85 g, and only signet ring cell carcinomas and poorly differentiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…Healing and relapse of an ulcer inside the cancer focus, similar to the malignant cycle of cancer in the human stomach (Murakami 1968) [48], was observed in one beagle [32]. Similar follow-up studies were performed by Fujita et al [24], Sunagawa et al [50], Saito et al [33], Noguchi et al [34], and Xiao et al [27]. No definitive intestinalization of the gastric mucosa was detected in this series of canine experiments.…”
Section: Follow-up Studies Of Cancer Production By X-ray Endoscopy Asupporting
confidence: 65%
See 1 more Smart Citation
“…Healing and relapse of an ulcer inside the cancer focus, similar to the malignant cycle of cancer in the human stomach (Murakami 1968) [48], was observed in one beagle [32]. Similar follow-up studies were performed by Fujita et al [24], Sunagawa et al [50], Saito et al [33], Noguchi et al [34], and Xiao et al [27]. No definitive intestinalization of the gastric mucosa was detected in this series of canine experiments.…”
Section: Follow-up Studies Of Cancer Production By X-ray Endoscopy Asupporting
confidence: 65%
“…Sunagawa et al [22] investigated the effects of the duration of ENNG administration on histological tumor differentiation and found that a small dose of ENNG (3 months; total, 5.85 g) produced only undifferentiated adenocarcinomas in beagles, while differentiated adenocarcinomas developed with high doses (6 months; 11.7 g, and 9 months; 17.6 g). However, Sano et al [23] reported that a small dose (4 months; 7.65 g) resulted in the development of differentiated adenocarcinomas in 7 of the 21 dogs and that antral conditions, antral pH, the number of G-cells, achlorhydria, and hypergastrin, were significantly associated with the development of differentiated adenocarcinomas.…”
Section: Change In Enng Concentration and Duration Of Enng Feedingmentioning
confidence: 99%
“…Transition zone enrichment has been observed previously in gastric cancer models: dogs administered with the carcinogen N‐ethyl‐N′‐nitro‐N‐nitrosoguanidine (ENNG) for three months developed SRCCs exclusively in the antral mucosa immediately adjacent to the transition zone. ( 16 ) In mice with conditional inactivation of the bone morphogenetic protein receptor Bmpr1a , tumors develop specifically at both the gastric squamocolumnar and gastrointestinal transition zones. ( 17 ) Similarly, mice that have been exposed to the carcinogen N‐nitroso‐N‐butylurea ( 18 ) or have a specific Smad4 mutation ( 19 ) also develop tumors which are observed primarily in the gastrointestinal transition zone.…”
Section: Hdgc Clinical Features and Pathologymentioning
confidence: 99%
“…( 11,13 ) A comparable pattern of SRCC development has been described by Sunagawa et al . in the ENNG‐induced canine gastric cancer model ( 16 ) and by Sugihara et al . in human sporadic SRCC.…”
Section: Proposed Mechanism Of Hdgc Initiationmentioning
confidence: 99%
“…Alkylating carcinogen, Nmethyl-N'-nitro-N-nitrosoguanidine (MNNG) is well known to cause malignant tumors in the stomach of rats by oral administration 20) . Similarly, its ethyl homolog, ENNG, induces gastric tumors in mice, rats, dogs, or monkeys [21][22][23] . ENNG is more effective than MNNG for the induction of duodenal tumors when continuous doses were administered orally to mice 21,24) .…”
Section: Introductionmentioning
confidence: 99%